2016
DOI: 10.1371/journal.pone.0145955
|View full text |Cite
|
Sign up to set email alerts
|

Particle Pollution Estimation Based on Image Analysis

Abstract: Exposure to fine particles can cause various diseases, and an easily accessible method to monitor the particles can help raise public awareness and reduce harmful exposures. Here we report a method to estimate PM air pollution based on analysis of a large number of outdoor images available for Beijing, Shanghai (China) and Phoenix (US). Six image features were extracted from the images, which were used, together with other relevant data, such as the position of the sun, date, time, geographic information and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 29 publications
2
67
0
Order By: Relevance
“…In order to understand which features can affect PM 2.5 concentrations when using image processing methods, previous research has pointed out that the PM 2.5 concentrations may affect image characteristics, including the distance, hazy model, entropy, contrast, sky color, and solar zenith angle. It was found that the distance is the feature that has the most influence [28]. This is consistent with the definition of visibility, and a previous study has also shown that visibility can be estimated using high-frequency information from an image [22].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In order to understand which features can affect PM 2.5 concentrations when using image processing methods, previous research has pointed out that the PM 2.5 concentrations may affect image characteristics, including the distance, hazy model, entropy, contrast, sky color, and solar zenith angle. It was found that the distance is the feature that has the most influence [28]. This is consistent with the definition of visibility, and a previous study has also shown that visibility can be estimated using high-frequency information from an image [22].…”
Section: Introductionsupporting
confidence: 86%
“…This is consistent with the definition of visibility, and a previous study has also shown that visibility can be estimated using high-frequency information from an image [22]. The region of interest (RoI) has also been manually selected to estimate PM 2.5 concentrations [28]. However, the estimation performance might be degraded because of such a manually selected RoI.…”
Section: Introductionsupporting
confidence: 77%
“…Liu et al [30] has proposed an image-based approach, while considering several image features, such as transmission, sky smoothness, image color, entropy, contrast, time, geographical location, sun, and weather condition to predict the PM 2.5 of the air. They have developed a regression model that is based on these features to predict PM level from photos of Beijing, Shanghai, and Phoenix over a one-year period.…”
Section: Related Workmentioning
confidence: 99%
“…This dataset contains 1954 real images, with dimensions 584 x 389 and RGB color space, of the Oriental Pearl Tower, Shanghai, China [30]. These images, which were collected from Archive of Many Outdoor Scenes (AOMS) dataset, are hourly images that are captured every hour from 08:00 to 16:00 hrs during May to December in 2014 [55].…”
Section: Shanghai City Datasetmentioning
confidence: 99%
“…Apart from the applications mentioned, several studies were carried out regarding the estimation of air quality from images. In [21], the authors utilize six image features together with additional information such as the position of the sun, date, time, geographic information and weather conditions, etc., to estimate the amount of PM 2.5 (particles with aerodynamic diameter less than 2.5 micrometers) in the air. Experimental results have shown that the image analysis method is able to estimate the PM 2.5 index accurately.…”
Section: Related Workmentioning
confidence: 99%